An Experimental Model of Neuromyelitis Optica Spectrum Disorder–Optic Neuritis: Insights Into Disease Mechanisms - Soerensen, Sofie Forsberg; Wirenfeldt, Martin; Wlodarczyk, Agnieszka; Moerch, Marlene Thorsen; Khorooshi, Reza; Arengoth, Dina S.; Lillevang, Soeren Thue; Owens, Trevor; Asgari, Nasrin (Frontiers in Neurology, 2021)
Background: Optic neuritis (ON) is a common inflammatory optic neuropathy, which often occurs in neuromyelitis optica spectrum disease (NMOSD). An experimental model of NMOSD-ON may provide insight into disease mechanisms. Objective: To examine the pathogenicity of autoantibodies targeting the astrocyte water channel aquaporin-4 [aquaporin-4 (AQP4)-immunoglobulin G (AQP4-IgG)] in the optic nerve. Materials and Methods: Purified IgG from an AQP4-IgG-positive NMOSD-ON patient was together with human complement (C) given to wild-type (WT) and type I interferon (IFN) receptor-deficient mice (IFNAR1-KO) as two consecutive intrathecal injections into cerebrospinal fluid via cisterna magna. The optic nerves were isolated, embedded in paraffin, cut for histological examination, and scored semi-quantitatively in a blinded fashion. In addition, optic nerves were processed to determine selected gene expression by quantitative real-time PCR. Results: Intrathecal injection of AQP4-IgG+C induced astrocyte pathology in the optic nerve with loss of staining for AQP4 and glial fibrillary acidic protein (GFAP), deposition of C, and demyelination, as well as upregulation of gene expression for interferon regulatory factor-7 (IRF7) and CXCL10. Such pathology was not seen in IFNAR1-KO mice nor in control mice. Conclusion: We describe induction of ON in an animal model for NMOSD and show a requirement for type I IFN signaling in the disease process.